2012
DOI: 10.14341/2072-0351-5536
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of proinflammatory factors in patients with progressive angina pectoris and type 2 diabetes mellitus

Abstract: Aims. Our study was aimed to assess the influence of non-specific inflammation and endothelial dysfunction on developmentof cardiovascular events in patients with type 2 diabetes mellitus (T2DM) and progressive angina pectoris. Materials and methods. 140 patients (63 of them were also diabetic) received follow-up for cardiovascular events during12 months after an episode of unstable angina pectoris. Upon hospitalization for acute coronary syndrome analyses wereperformed to assess the degree of systemic infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…During the investigation of indicators of oxidative stress in patients with myocardial infarction (MI), it was revealed that patients with complicated postinfarction period are characterized by a significant increase in the activity of lipid peroxidation (LPO) and a decrease in antioxidant protection [2] .The predictive role of systemic inflammation in hyperglycemic conditions is confirmed by a number of studies. So it was found that patients after an episode of unstable angina pectoris in combination with diabetes had higher values of indicators of inflammation markers, which were associated with a complicated course of the hospital period, in contrast to patients without carbohydrate metabolism disorders (CMD) [1]. Moreover, role of complex immune reactions in the processes of atherogenesis is beyond doubt.…”
Section: Introductionmentioning
confidence: 99%
“…During the investigation of indicators of oxidative stress in patients with myocardial infarction (MI), it was revealed that patients with complicated postinfarction period are characterized by a significant increase in the activity of lipid peroxidation (LPO) and a decrease in antioxidant protection [2] .The predictive role of systemic inflammation in hyperglycemic conditions is confirmed by a number of studies. So it was found that patients after an episode of unstable angina pectoris in combination with diabetes had higher values of indicators of inflammation markers, which were associated with a complicated course of the hospital period, in contrast to patients without carbohydrate metabolism disorders (CMD) [1]. Moreover, role of complex immune reactions in the processes of atherogenesis is beyond doubt.…”
Section: Introductionmentioning
confidence: 99%
“…Прогностическая роль системного воспаления в условиях гипергликемии подтверждается рядом проведенных исследований. Так установлено, что пациенты после перенесенного эпизода нестабильной стенокардии в сочетании с СД имели более высокие значения показателей маркеров воспаления, которые ассоциировались с осложненным течением госпитального периода, в отличии от больных без нарушения углеводного обмена (НУО) [1]. Кроме того, роль комплексных иммунных реакций в процессах атерогенеза не вызывает сомнений.…”
unclassified
“…. Была показана связь СЛСИ с субклиническими поражениями сердца [7], распространенностью коронарного [8] и некоронарного [9] атеросклероза. До настоящего времени лишь единичные работы посвящались изучению роли данного индекса у неврологических больных [10][11][12].…”
unclassified